ROLE OF FDI IN ENCOURAGING HOSPITALITY SECTOR IN THE CHANGING ECONOMIC ENVIRONMENT: AN EMPIRICAL STUDY - Pallathadka, Harikumar; Kirana Pallathadka, Laxmi (The journal of contemporary issues in business and government, 2022)
Foreign investors invest their resources to earn profits out of the revenue incurred while strengthening the hospitality industry. Foreign Direct Investment is characterized as unfamiliar financial investors blending their resources into another nation with command over the administration of resources and benefits. For the most part, it is a fact that the more FDI a nation obtains, the more is the chance to develop economically. Financial development could create a nation full of opportunities. FDI frequently brings enormous amounts of assets, and new innovations to the nation, just as cutting edge board abilities permit nearby enterprises and areas to acquire a great deal of involvement (Mason & Brown, 2014). The hospitality sector has been developing efficiently and effectively in the current years, and it has been generating lots of wealth from other countries. Foreign direct investment promotes employment and has given rise to colossal human resources available in the hospitality sector. This paper aims at portraying a view of FDI and its role in fostering the hospitality industry in a dynamic economic ecosystem. A sample of 190 people from the hospitality sector was surveyed to know the role and significance of FDI in Encouraging the Hospitality Sector in the Changing Economic Environment. Mean, and the test was applied to analyze the data and reach results. It is found that FDI plays a significant role by encouraging the Hospitality Sector in the Changing Economic Environment.